Personal Disposition of Bachelor Nursing Students Regarding the Care of Advance Age People in Nobel Medical College Teaching Hospital - Jha, Nilam Kumari; Jha, Komal Kant (Journal of Nobel Medical College, 2020)
Background: Older people have complex requirements arising from future conditions. Nursing services regarding the care of advance age population is really important in to the readiness of nursing student. Materials and Methods: A cross-sectional study was conducted in Nobel Medical College Teaching Hospital, Biratnagar, Nepal from February to July 2020. A total of 118 Bachelor nursing students were selected by using a non- probability consecutive sampling technique. Data was collected by using Personal disposition regarding care of advance age people were evaluated by using standardized tool, Nolan’s Intent to work with older people questionnaire. All calculations and statistical analysis are processed by the SPSS 22.0. Results: It showed that personal disposition of regarding care of advance age people were negative perception about 51.7%. Among variable, age and study year were significantly associated with personal disposition (p=< 0 .001). However, there was no significant result showed between the family type, nursing programme and prior experience with advance age. Conclusion: The study concluded that the Bachelor nursing students had relatively negative personal disposition regarding care of advance age people. More study is important to higher understand students’ experiences and insight. These must certainly be augment to strengthen an result that is improved is clinical the look after the older grownups.